ANALISIS SAINS TERHADAP PENDAPAT BEBERAPA MUFASIR DALAM MENJELASKAN QS. YAASIIN AYAT 80 TENTANG BAHAN BAKAR - Saepulloh, Saepulloh (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
The diversity of thought patterns among the interpreter of HolyQur'an in interpreting verses, especially with regard to the scientificmiracles of the Qur'an is something interesting to study. The Qur'anwas revealed not to explain science, but as a guide for those who arepious. However, many of the verses of the Qur'an are calling forthinking, so it is inevitable that the motivation of the exegete to studyverse by verse will continue to develop in harmony with scientificdisciplines, trends, and the development of science and technology intheir lifetime.The problem in this research is the differences of opinion someinterpreters of Holy Qur'an are quite significant in interpreting QS.Yaasiin verse 80, by raising six opinions of the interpreter of HolyQur'an representing classical and contemporary of interpreters of HolyQur'an.The purpose of this study is to uncover the background of theHoly Quran's interpreters dissent, looking for points of similaritythrough scientific analysis. Thus, this research includes qualitativeresearch with a literature study approach. The primary data sourcesare obtained from the Qur'an commentaries, science books and othersources.The research step starts from the presentation of data fromseveral Holy Quran's interpreters in the study of the verse under studyalong with the bibliography to determine the development of science in Thoriqotuna | Jurnal Pendidikan Islamits time. Then these opinions are clarified to find out the differencesand similarities, then reviewed through a scientific analysis approach.From the results of the study, identified three main opinions ofHoly Qur'an's interpreters in interpreting the QS. Yaasiin paragraph80, namely; First, opinions about the fuel of al-‘afar and al-marh (atype of green plants in the country of Hijaz). Second, the opinion thatstates fuel in the process of photosynthesis, and the third opinion aboutfuel in the form of coal.The results of the study showed a relationship (equation)between these commentaries in terms of the energy products producedand their utilization. Different in terms of the shape of the fuel, but themolecular structure (atom C), the combustion process (O2 as anoxidizer) and the product of combustion (CO2 + H2O + E) are thesame. Thus, scientific analysis makes the same concept from theopinions of several different interpreters of Holy qur'an.